Insights Into the Sunlight-Driven Water Oxidation by Ce and Er-Doped ZrO2 - Hernández, Simelys; Gionco, Chiara; Husak, Thomas; Castellino, Micaela; Muñoz-Tabares, José A.; Tolod, Kristine R.; Giamello, Elio; Paganini, Maria C.; Russo, Nunzio (Frontiers in Chemistry, 2018)
In the present work, the activity of Ce and Er-doped ZrO2 nanopowders for sun-driven photocatalytic water oxidation has been investigated. ZrO2 powders with tunable amounts of tetragonal, monoclinic and cubic polymorphs have been synthesized by introducing Ce and Er (from 0.5 to 10 mol % on an oxide basis) through hydrothermal method. The aim of this work is to investigate the role of rare earth (RE) ions rich of 4f electrons (Er3+) and with entirely empty 4f levels (Ce4+) in the ZrO2 matrix for the sun-driven photocatalytic water oxidation reaction. The samples have been characterized by means of UV-Vis spectroscopy, X-Ray diffraction (XRD), N2 adsorption, X-ray photoelectron spectrophotometry (XPS) and transmission electronic microscopy (TEM) with energy dispersive spectroscopy (EDS). With respect to the bare ZrO2 mainly containing monoclinic (m-) phase, an increasing amount of rare-earth (RE) dopant was found to improve the specific BET surface area and to stabilize the tetragonal (t-) or cubic (c-) polymorphs of ZrO2 at room temperature. XRD data confirmed that dopants were mainly inserted in the t-ZrO2 phase. The photocatalytic O2 evolution from water under AM 1.5 G simulated sunlight illumination of the prepared samples have been correlated with their optical, structural and chemical properties. The effect of the dopant concentration on the chemical-physical and photocatalytic properties of the Er- and Ce-doped ZrO2 materials was elucidated. The samples with 5% of RE oxide were the most active, i.e. three times more than pure zirconia. Their superior photocatalytic activity was found to be mainly correlated to two factors: i) an optimal surface concentration of RE ions of about 3.7 %, which increased charge carriers separation in the photocatalysts surface due more superficial defects of the t-ZrO2 and a higher surface area, thus enhancing the reaction kinetics, ii) a controlled amount of monoclinic vs. tetragonal (or cubic) polymorphs of zirconia with an optimum ratio of about 70/30 of t-ZrO2/m-ZrO2. Instead, the increased ability of the RE-doped ZrO2 to harvest visible light was found to have a secondary role on the photocatalytic activity of the Ce-doped ZrO2 material.